Segregation for persistent neutral (Hermaphrodite) flowers and male bracts in plantain-banana hybrids - Ortíz, R. (1996)
The aim of the work was to study the genetic origin of the persistence of male bracts and neutral flowers in diploid bananas bred by crossing diploids and tetraploids. The genetic system proposed for somaclonal variation and evolution in triploid bananas is described.